2006
DOI: 10.1158/0008-5472.can-05-2606
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Myofibroblasts in Prostaglandin E2–Stimulated Intestinal Epithelial Proliferation and Angiogenesis

Abstract: Prostaglandins (PG) are produced throughout the gastrointestinal tract and are critical mediators for a complex array of physiologic and pathophysiologic processes in the intestine. Intestinal myofibroblasts, which express cyclooxygenase (COX) and generate PGE 2 , play important roles in intestinal epithelial proliferation, differentiation, inflammation, and neoplasia through secreting growth factors and cytokines. Here, we show that PGE 2 activated human intestinal subepithelial myofibroblasts (18Co) through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 62 publications
3
69
1
2
Order By: Relevance
“…Chemokine CXCL1 (growth-regulated oncogene-␣) can be induced by PGE 2 in colon cancer cells, which then promotes neoangiogenesis in intestinal neoplasia via a paracrine pathway (37). Amphiregulin, hepatocyte growth factor, and VEGF are induced by PGE 2 in intestinal subepithelial myofibroblasts, which stimulate the growth of intestinal epithelial cells and promote angiogenesis through a paracrine mechanism (38). In the present study, we added the proinflammatory cytokine IL-1␣ to the list of growth factors/cytokines, which are induced by PGE 2 and mediate PGE 2 proneoplastic actions through autocrine or paracrine mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Chemokine CXCL1 (growth-regulated oncogene-␣) can be induced by PGE 2 in colon cancer cells, which then promotes neoangiogenesis in intestinal neoplasia via a paracrine pathway (37). Amphiregulin, hepatocyte growth factor, and VEGF are induced by PGE 2 in intestinal subepithelial myofibroblasts, which stimulate the growth of intestinal epithelial cells and promote angiogenesis through a paracrine mechanism (38). In the present study, we added the proinflammatory cytokine IL-1␣ to the list of growth factors/cytokines, which are induced by PGE 2 and mediate PGE 2 proneoplastic actions through autocrine or paracrine mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…These cells share many of the structural and functional characteristics of in situ colonic subepithelial myofibroblasts, including a reversible stellate morphology, ␣-smooth actin expression, and the presence of multiple cell surface receptors (51). 18Co cells provide a model to elucidate physiological and pathophysiological functions of intestinal subepithelial myofibroblasts and, accordingly, have been used extensively to study colonic myofibroblast function in a variety of settings (22,33,42). 18Co cells were maintained at 37°C in Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% fetal bovine serum (FBS) in a humidified atmosphere containing 10% CO 2 and 90% air.…”
Section: Methodsmentioning
confidence: 99%
“…Eicosanoids derived from both stromal and epithelial cells may stimulate stromal cells to release growth factors, which, in turn, provide a pro-proliferative and pro-neoplastic environment for the intestinal epithelium. Shao et al [28] found that exogenous PGE 2 induced the expression and secretion of several pro-proliferative and pro-angiogenic growth factors such as amphiregulin, vascular endothelial growth factors, hepatocyte growth factor and neuregulins by intestinal subepithelial myofibroblasts, which may mediate intestinal epithelial growth and transformation. Finally, we must consider that activated macrophages also produce eicosanoids [29] that are present near the epithelial progenitor niche [30].…”
Section: Role Of Eicosanoids In the Control Of Intestinal Epithelial mentioning
confidence: 99%